Redescription of Hemileius suramericanus (Acari, Oribatida, Scheloribatidae) with comments about Neotropical congeneric species - Natalia A. Fredes; Pablo A. Martínez (Persian Journal of Acarology)
This paper represents the first redescription of Hemileius suramericanus (Hammer, 1958) (Oribatida, Scheloribatidae). Morphological and chaetotactic details are added to original Hammer's description. The species is compared with others Neotropical species of Hemileius and two new synonyms, H. laticlava and H. confundatus sensu Hammer, are proposed.